ANALISIS BERPIKIR KREATIF SISWA KELAS II SD DALAM MENYELESAIKAN SOAL PERKALIAN - Haerunissa, Rona; Moh. Toharudin; Muamar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe the creative thinking skills of second-grade students of Karangjunti 01 Elementary School in solving multiplication problems and identify the factors that influence them. This study uses a qualitative approach in a case study method. The subjects in this study consisted of four students and one class teacher. Data collection techniques were carried out through interviews, observations, and documentation. Creative thinking skills were analyzed based on four indicators, namely, fluency, flexibility, elaboration, and originality. The results of the study indicate that students' creative thinking skills are still relatively low. The majority of students have not been able to demonstrate various solution strategies, are not accustomed to explaining steps in sequence, and lack the confidence to try different methods. Only one student fulfilled all the indicators of creative thinking. Factors that influence low student creativity consist of three aspects, namely, cognitive factors (limited alternative strategies), affective factors (low self-confidence), and contextual factors (minimal use of technological media). These findings indicate that the development of students' creativity in mathematics learning needs to be supported through an active, varied, and contextual approach to encourage students' courage in thinking openly and solving problems in creative ways.